FLAVONOIDS, ANTI-INFLAMMATORY ACTIVITY AND CYTOTOXICITY OF MACFADYENA UNGUIS-CATI L. - Aboutabl, E. A.; Hashem, Fatma A.; Sleem, A. A.; Maamoon, A. A. (African Journal of Traditional, Complementary and Alternative Medicines, 2007)
Ethyl acetate and ethanol extracts of unflowering aerial part of Macfadyena unguis-cati L.(Fam. Bignoniaceae) were found to be rich in phenolic compounds. From ethyl acetate extract,six flavonoids were identified, 8, methoxy, acacetin, 7-O glucoside; 6, methoxy apigenin 7-O glucoside; 4`-O methyl scutellarin, 6-O apiosyl galactoside; acacetin, 7-O glucosyl, 8-C rhamnosyl, 3-O- arabinofuranoside; 4`-methyl, 6- methoxy kaempferol, 7-O, 8-C diglucoside and vicenin II were isolated, while 6, methoxy, acacetin 7-O glucoside; and quercitrin were isolated from ethanol extract. These compounds were characterized and identified by their physicochemical and spectral data. The crude ethanol extract exhibited significant anti-inflammatory activity (80.47%) and moderate cytotoxic activity against lung cell line.